Nurses' experiences with continuous vital sign monitoring on the general surgical ward: a qualitative study based on the Behaviour Change Wheel - J. P. L. Leenen; E. M. Dijkman; A. van Hout; C. J. Kalkman; L. Schoonhoven; G. A. Patijn (BMC, 2022)
Abstract Background To support early recognition of clinical deterioration on a general ward continuous vital signs monitoring (CMVS) systems using wearable devices are increasingly being investigated. Although nurses play a crucial role in successful implementation, reported nurse adoption and acceptance scores vary significantly. In-depth insight into the perspectives of nurses regarding CMVS is lacking. To this end, we applied a theoretical approach for behaviour change derived from the Behaviour Change Wheel (BCW). Aim To provide insight in the capability, opportunity and motivation of nurses working with CMVS, in order to inform future implementation efforts. Methods A qualitative study was conducted, including twelve nurses of a surgical ward in a tertiary teaching hospital with previous experience of working with CMVS. Semi-structured interviews were audiotaped, transcribed verbatim, and analysed using thematic analysis. The results were mapped onto the Capability, Opportunity, Motivation - Behaviour (COM-B) model of the BCW. Results Five key themes emerged. The theme 'Learning and coaching on the job' linked to Capability. Nurses favoured learning about CVSM by dealing with it in daily practice. Receiving bedside guidance and coaching was perceived as important. The theme 'interpretation of vital sign trends' also linked to Capability. Nurses mentioned the novelty of monitoring vital sign trends of patients on wards. The theme 'Management of alarms' linked to Opportunity. Nurses perceived the (false) alarms generated by the system as excessive resulting in feelings of irritation and uncertainty. The theme 'Integration and compatibility with clinical workflow' linked to Opportunity. CVSM was experienced as helpful and easy to use, although integration in mobile devices and the EMR was highly favoured and the management of clinical workflows would need improvement. The theme 'Added value for nursing care' linked to Motivation. All nurses recognized the potential added value of CVSM for postoperative care. Conclusion Our findings suggest all parts of the COM-B model should be considered when implementing CVSM on general wards. When the themes in Capability and Opportunity are not properly addressed by selecting interventions and policy categories, this may negatively influence the Motivation and may compromise successful implementation.